“Òrìsà Ńjẹ, Ilé Asé Ńjẹ- Os Orixás Comem, O Terreiro Come”: uma etnografia da sacralização de animais em um Terreiro de Umbanda Traçada - Silva, Julia Aparecida Rodrigues da (2024)
In the rituals of African religions, the sacralization of animals is an essential element in the connection between humans and deities: by immolating specific animals, the aim is to offer (feed) the deity and then distribute the animal's meat to everyone in the terreiro community and other followers present. Through sacralization (sacrifice), the animal's axé will serve as food for the Orixá (and for humans) because it acts and operates certain energy flows. The aim of this ethnography is to understand the foundations and purposes that animal life acquires during the ritual of sacralization in Candomblecist cosmology: where the animal is acquired, the care and place of its stay in the terreiro before undergoing immolation, who immolates and which species are immolated, the precautions (preceito) taken by the Afro-religious, the instruments and supplies that are part of the ritual, the songs and prayers chanted and finally, after the sacralized animal, how the Orixá and the terreiro eat. And finally, to analyze the debates surrounding the political arguments, mostly Christian, that have tried and are trying to ban this practice on the grounds that it is animal cruelty, as well as to verify the importance of this ritual in the view of religious practitioners and their communication with the spiritual plane.